2023
DOI: 10.7759/cureus.33879
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of FGF-23 With Biochemical Markers and Bone Density in Chronic Kidney Disease-Bone Mineral Density Disorder

Abstract: The purpose of this study was to determine the relationship between biochemical markers such as serum calcium (Ca), phosphorus (P), intact parathyroid hormone (iPTH), 25(OH) vitamin D, and fibroblast growth factor 23 (FGF23) in our study group, as well as to correlate dual-energy X-ray absorptiometry (DEXA) findings with these biochemical markers. MethodologyAn eligible group of 50 chronic hemodialysis (HD) patients, age 18 and older, who have undergone HD two times a week for at least six months participated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Interestingly, we did not observe any significant correlation between 25 vitamin D levels and BMD in the multivariate analysis. However, a recent study evaluating 50 HD patients showed no significant association between vitamin D levels and BMD status [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, we did not observe any significant correlation between 25 vitamin D levels and BMD in the multivariate analysis. However, a recent study evaluating 50 HD patients showed no significant association between vitamin D levels and BMD status [ 36 ].…”
Section: Discussionmentioning
confidence: 99%